2021
DOI: 10.1021/acs.langmuir.1c00170
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Substrate Cues for Co-Culturing Cells in a Micropattern

Abstract: Spatial distribution of cells and their interactions between neighboring cells in native microenvironments are of fundamental importance in determining cell fate decisions such as migration, growth, and differentiation. Controlling the spatial distribution of different cell types in defined geometries can replicate these native environments, which can be a useful model for several studies. While spatiotemporal control over multiple cell arrangements is required to achieve the complex tissue architecture, unfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…In our previous study, we have demonstrated the effect of these geometrical cues toward the behavior of osteoblast and fibroblast cells and utilized these effects to develop a model to coculture cells, but the effect of these cues in guiding a biological process such as differentiation was not studied. 32 The study also demonstrated how these cues can influence cellular morphology between the cells present at the center vs the edges and how these patterns can be transmitted to a cell seeded after a time interval, which further allows self-patterning of a second cell type. We hypothesized that cell alignment at the corner/edges signals the subsequently seeded cells to align according to the pattern due to cell−cell signaling.…”
Section: ■ Materials and Methodsmentioning
confidence: 84%
“…In our previous study, we have demonstrated the effect of these geometrical cues toward the behavior of osteoblast and fibroblast cells and utilized these effects to develop a model to coculture cells, but the effect of these cues in guiding a biological process such as differentiation was not studied. 32 The study also demonstrated how these cues can influence cellular morphology between the cells present at the center vs the edges and how these patterns can be transmitted to a cell seeded after a time interval, which further allows self-patterning of a second cell type. We hypothesized that cell alignment at the corner/edges signals the subsequently seeded cells to align according to the pattern due to cell−cell signaling.…”
Section: ■ Materials and Methodsmentioning
confidence: 84%
“…One of the main characteristics of a biomaterial is the ability to support cell adhesion, proliferation, and migration without causing any cytotoxic effects. 49 The viability of the cells were studied via live (calcein AM) and dead (propidium iodide, PI) staining. As seen from Figure 3a, the cells showed increased viability in all three scaffolds (AL, AS, ApS) after 7 days of culture.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main characteristics of a biomaterial is the ability to support cell adhesion, proliferation, and migration without causing any cytotoxic effects . The viability of the cells were studied via live (calcein AM) and dead (propidium iodide, PI) staining.…”
Section: Resultsmentioning
confidence: 99%
“…A skin substitute that promotes migration of cells involved in skin repair may lead to faster and higher-quality wound closure. Hence, the tip of each pyramid was around 150 μm so that there is some area for the cells to adhere, and the tapered geometry provided a gradient to enhance the cell migration , (Figure S4). To check the stability of the micro-pyramids, the dressings were immersed in PBS for 7 days.…”
Section: Resultsmentioning
confidence: 99%